Comparative analysis of tomato value chain competitiveness in selected areas of Malawi and Mozambique - Nelson Mango; Lawrence Mapemba; Hardwick Tchale; Clifton Makate; Nothando Dunjana; Mark Lundy (Cogent Economics & Finance, 2015)
This paper discusses tomato value chain performance in Malawi and Mozambique using data collected from a market study commissioned by the International Centre for Tropical Agriculture as part of a regional research on conservation agriculture in maize-based farming systems in Sub-Saharan Africa. The results show that Malawi has a slightly higher competitive advantage in the production of tomato compared to Mozambique. Malawi's relative competitiveness in tomato is mainly due to slightly higher productivity and the cost advantage in labor (low wages) and irrigation costs. The paper proposes policy implications aimed at raising the productivity and trade competitiveness of tomato, as this will ensure the overall productivity of the maize-based smallholder farming systems in the two countries.
Keywords: 330; tomato; value chain; competitiveness; Malawi; Mozambique